Constructing Identities at Work
XIV, 248 p.
Keywords: This edited collection presents cutting edge research on the process of identity construction in professional and institutional contexts, from corporate workplaces, to courtrooms, classrooms, and academia. The chapters consider how interactants do identity work and how identity is indexed (often in subtle ways) in workplace discourse.